The essential fatty acids - revisited - Rajion, Mohamed Ali (2003)
Since the discovery of the essential fatty acids (EFA) namely linolenic acid (18:2n-6) and {X-linolenic acid (18:3n-3) in 1929 there has been a tremendous amount of research carried out on their possible sources, metabolism, physiological functions, deficiency symptoms, status assessments and dietary requirements for most animal species including man. They are termed essential fatty acids as they cannot be synthesised by the mammalian cellular system and must be derived from dietary sources. They are also essential functionally as they are required for the well being and health of the animals, including man.